Case report: ranavirus infections in captive eastern box turtles (Terrapene carolina carolina) in Japan - Tamukai, Kenichi; Shimoda, Hiroshi; Kadekaru, Sho; Une, Yumi (Frontiers in Veterinary Science, 2025)
Ranaviruses are broad host-range pathogens that cause fatal infections in ectothermic vertebrates, including fish, amphibians, and reptiles and are considered emerging infectious diseases. This report describes a case of ranavirus infection identified at a box turtle breeding facility in Japan. Of 12 box turtles, representing three species and housed in a mixed-species outdoor pen, all six eastern box turtles (Terrapene carolina carolina) exhibited clinical signs, and three died. Severe clinical signs in four turtles included nasal and oral discharge and palpebral edema, while two showed only oral discharge. No other species were affected. The oral and tongue mucosa were enlarged or partially eroded, with their surfaces covered by a pseudomembranous crust containing fibrin, heterophils, necrotic material, and multifocal bacterial colonies. Multifocal necrosis was observed in both the spleen and liver; however, no inclusions were detected in any affected tissues. Electron microscopy revealed cytoplasmic ranavirus-like particles within necrotic spleen cells. Ranavirus infection was confirmed by PCR, and partial genome sequencing identified a strain similar to frog virus 3 (FV3).